The design and environmental aspects of the prayer room / Abu Bakar Abd Hamid … [et al.] - Abd Hamid, Abu Bakar; Mohd Taib, Mohd Zafrullah; Abdul Wahab, Mohamad Hanif; Alias, Aida (Division of Research and Industry Linkages, UiTM Melaka, 2014)
Malaysia aims to achieve its developed nation status by year 2020. Amidst the rapid expansion of high-tech skyscraper buildings, commercial midpoints and vibrant education centers, the religion of Islam holds priority in the current modem development. Islamic-prayers or 'solah' is one of the primary and very important in the daily rules of a Muslim. Muslims throughout the world perform 'solah' (prayer) five times a day in certain positions and several steps that should be carried out before prayer, including wudhu' (ablution) and covering one's body. Provision of prayer areas for Muslims in modern commercial buildings need to be highlighted. Although today Muslim prayer areas are provided in almost every shopping center but it is in great need of attention. It was observed that design guidelines have not been fully implemented and some are not compliance to the Islamic requirements. In this study, the scope will cover on the function and design of prayer areas or 'musolla' in shopping centers. The information and data collected in this study will be use as a guideline for the implementation of the respected parties such as Local Authorities and Architects / Designers.